Combining Pasture- and Animal-Based Factors to Predict Herbage or Dry Matter Intake of Lambs Grazing on Cocksfoot, Meadow Fescue and Tall Fescue Pastures - Ahmet Akdağ; Nuh Ocak; İbrahim Aydın (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to establish the correlations between actual dry matter intake (DMI) and some animal (body weight, (BW)) and pasture (crude protein (CP); neutral detergent fiber (NDF); in vitro dry matter digestibility (IVDMD); dry matter yield (DMY); herbage allowance (HA); herbage mass (HM); metabolizable energy (ME); relative forage quality (RFQ); total digestible nutrients (TDN)) based factors to formulate precise regression equations for DMI prediction. For this purpose, data (n = 36, 2 years × 3 blocks × 6 data collection) were utilized for two grazing seasons (2020–2021) on cocksfoot (Dactylis glomerata), meadow fescue (Festuca pratensis) and tall fescue (Festuca arundinacea) mixed pastures with Karayaka male lambs at an average age of 2 months for 60 days in each season. Positive correlations were determined between DMI and BW (0.777), HA (0.814), DMY (0.844), and NDF (0.609), while DMI had negative correlations with IVDMD (-0.738), RFQ (-0.357), CP (-0.209), TDN (-0.177) and ME (-0.039). In addition, animal and pasture–based factors were evaluated by principal component analysis to determine the in–cooperating variables in variance. As a result, equations were developed by using parameters with high correlation coefficient and the best–fit 3 equations for predicting DMI of lambs grazing cocksfoot, meadow fescue and tall fescue pastures: (I) -1224.09 + 39.90BW (kg) + 33.69HA (kg DM/ kg BW) + 8.22NDF (% of DM), r2=0.815, II) -701.47 + 18.96BW (kg) + 673.61DMY (kg/ per square meters) + 8.19NDF (% of DM), r2=0.807, III) -325.32 + 43.49HA (kg DM/kg BW)-2.21IVDMD (%) + 8.57NDF (%), r2=0.786).